2009
DOI: 10.1080/10584580903324675
|View full text |Cite
|
Sign up to set email alerts
|

PHASE TRANSITIONS IN Na1/2Bi1/2TiO3-SrTiO3-PbTiO3 SOLID SOLUTIONS

Abstract: Studies of nature of polarization in ternary solid solutions of Na 1/2 Bi 1/2 TiO 3 -SrTiO 3 -PbTiO 3 were done, using measurements of dielectric properties and polarization hysteresis loops. Various stages of relaxor behavior depending on concentration of PbTiO 3 were established and compared with other known ferroelectric relaxors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…2. For lower level of substitution (12.5%) for all Me 1+ the general features of the starting composition [11], such as frequency-dependent maximum of dielectric permittivity at temperature T m and a characteristic jump/drop, related to spontaneous phase transition between relaxor and ferroelectric state, at temperature T t <T m , where difference T m -T t is rather small, are preserved ( Fig. 2).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…2. For lower level of substitution (12.5%) for all Me 1+ the general features of the starting composition [11], such as frequency-dependent maximum of dielectric permittivity at temperature T m and a characteristic jump/drop, related to spontaneous phase transition between relaxor and ferroelectric state, at temperature T t <T m , where difference T m -T t is rather small, are preserved ( Fig. 2).…”
Section: Resultsmentioning
confidence: 81%
“…Earlier we have shown that partial replacement of Sr with Pb in initial solid solution 0.4NBT-0.6SrTiO 3 induces sequential transfer from relaxor to ferroelectric state, passing through characteristic stages of relaxor ferroelectricity [11,12]. Particularly for 0.4NBT-0.4SrTiO 3 -0.2PbTiO 3 the spontaneous transfer between relaxor and ferroelectric state at temperature T t is approaching the relaxing maximum of temperature dependence of dielectric permittivity at temperature T m .…”
Section: Introductionmentioning
confidence: 94%
“…Usually dielectric permittivity in relaxor ferroelectrics is described by static dielectric permittivity (ε s (T)) in temperature range, where it is frequency independent. In direction of low temperatures, dielectric permittivity ε (ω i ) at certain frequency ω i declines from ε s (T), starting from temperature T decl (ω i ) [1][2][3][4]. The temperature and frequency range of declining can be expressed as follows:…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they are also very valuable in the research of ferroelectric phase transitions in the presence of heterovalent ion disorder in the perovskite A-sublattice. Previously, we have reported on intriguing ternary solid solutions Na 1/2 Bi 1/2 TiO 3 -SrTiO 3 -PbTiO 3 exhibiting a wide range of relaxor behaviour depending on the concentration of the components [1,2]. Passing various stages of relaxor state stability as a function of Pb concentration, T m becomes almost frequencyindependent for the composition 0.4Na 1/2 Bi 1/2 TiO 3 -0.4SrTiO 3 -0.2PbTiO 3 and approaches the phase transition temperature between relaxor and ferroelectric state (T t ).…”
Section: Introductionmentioning
confidence: 99%